Angstrom-scale flatness using selective nanoscale etching - Yatsui, Takashi; Saito, Hiroshi; Nobusada, Katsuyuki (Beilstein Journal of Nanotechnology, 2017)
The realization of flat surfaces on the angstrom scale is required in advanced devices to avoid loss due to carrier (electron and/or photon) scattering. In this work, we have developed a new surface flattening method that involves near-field etching, where optical near-fields (ONFs) act to dissociate the molecules. ONFs selectively generated at the apex of protrusions on the surface selectively etch the protrusions. To confirm the selective etching of the nanoscale structure, we compared near-field etching using both gas molecules and ions in liquid phase. Using two-dimensional Fourier analysis, we found that near-field etching is an effective way to etch on the scale of less than 10 nm for both wet and dry etching techniques. In addition, near-field dry etching may be effective for the selective etching of nanoscale structures with large mean free path values.
Keywords: Angstrom-scale flatness; optical near-field; wet etching

(untitled) - Betzig, E.; Chichester, R. J. (Science, 1993)

(untitled) - Fang, N.; Lee, H.; Sun, C.; Zhang, X. (Science, 2005)

(untitled) - Yatsui, T.; Sangu, S.; Kawazoe, T.; Ohtsu, M.; An, S. J.; Yoo, J.; Yi, G.-C. (Appl. Phys. Lett., 2007)

(untitled) - Yamaguchi, M.; Nobusada, K.; Kawazoe, T.; Yatsui, T. (Appl. Phys. Lett., 2015)

(untitled) - Yamaguchi, M.; Nobusada, K. (Phys. Rev. A, 2016)

(untitled) - Kirkengen, M.; Bergli, J.; Galperin, Y. M. (J. Appl. Phys., 2007)

(untitled) - Jung, J.; Trolle, M. L.; Pedersen, K.; Pedersen, T. G. (Phys. Rev. B, 2011)

(untitled) - Yamaguchi, M.; Nobusada, K. (Phys. Rev. B, 2016)

(untitled) - Yatsui, T.; Nomura, W.; Stehlin, F.; Soppera, O.; Naruse, M.; Ohtsu, M. (Beilstein J. Nanotechnol., 2013)

(untitled) - Yatsui, T.; Tsuboi, T.; Yamaguchi, M.; Nobusada, K.; Tojo, S.; Stehlin, F.; Soppera, O.; Bloch, D. (Light: Sci. Appl., 2016)

(untitled) - Kullmer, R.; Bäuerle, D. (Appl. Phys. A, 1987)

(untitled) - Nakagawara, S.; Goto, T.; Nara, M.; Ozawa, Y.; Hotta, K.; Arata, Y. (Anal. Sci., 1998)

(untitled) - Thomsen, C. L.; Madsen, D.; Poulsen, J. A.; Thøgersen, J.; Knak Jensen, S. J. (J. Chem. Phys., 2001)

(untitled) - Saito, K.; Ikushima, A. J. (Phys. Rev. B, 2000)

Atkins’ Physical Chemistry - Atkins, P.; de Paula, J. (Oxford University Press, 2010)

(untitled) - Chinen, H.; Mawatari, K.; Pihosh, Y.; Morikawa, K.; Kazoe, Y.; Tsukahara, T.; Kitamori, T. (Angew. Chem., Int. Ed., 2012)